Health Literacy Model to Improve Adolescent Reproductive Health - Nuraeni, Tating; Okvitasari, Yenny; Judijanto, Loso; Setianti, Yanti; Ulfah, Bardiati; Aisa, Sitti (Oshada, 2025)
Adolescent reproductive health is an important aspect of public health development in Indonesia, where many adolescents face challenges in accessing accurate information and health services. Lack of reproductive health education, cultural stigma, and limited access to health services exacerbate this problem, so comprehensive sexual education (CSE) and improvements in service delivery are needed. The development of a health literacy model that utilizes digital tools and educational resources is essential to empower adolescents to make informed decisions and reduce risks related to early sexual activity and other reproductive health problems.This study employs a mixed-methods approach, combining qualitative and quantitative techniques. The first stage uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) to test the impact of various factors on adolescent reproductive health literacy, while the second stage applies qualitative analysis using the Miles and Huberman Model to gain deeper insights into the collected data. The results of the study stated that the Adolescent Reproductive Health Literacy model through a factor-based approach that affects reproductive health literacy has the potential to increase adolescents' understanding of sexual and reproductive health. With a focus on key components such as the Kesprorem Team, Media Literacy Program, Reproductive Health Media Production, Adolescent Reproductive Health Campaign, and Reproductive Health Research, the program is expected to have a positive impact on adolescents at the village and school levels. Interrelated factors, such as knowledge, attitudes, media access, social support, policies, and technological innovations, work together to create an ecosystem that supports adolescent reproductive health literacy.